Strategi Optimalisasi Sistem Aplikasi SINOPEN untuk Meningkatkan Efisiensi Proses Non-Perizinan OSS di DPMPTSP Kota Padang - Anita Zulman; Syamsir Syamsir; Wahyu Shandi Kurniawan; Alex Putra; Pitri Andini; Richa Angelina; Syahrul Waldi (Ranah Research : Journal of Multidisciplinary Research and Development, 2023)
He development of increasingly sophisticated technology influences elements of people's lives, such as government governance in creating public services, such as policy licensing services used by the government or regional governments to control the negative impacts of social and economic activities. Online Single Submission (OSS) is a business permit issued by the ministry to carry out permits such as business development permits, etc. This research uses descriptive, qualitative methods, with data collection techniques in this research namely observation, interviews and documentation methods. Based on the research results, the implementation of OSS still has shortcomings such as the absence of a research permit feature for students or academic staff, practice permits for doctors and staff. other health problems, problems that prevent OSS from running perfectly, the emergence of non-OSS licensing innovations in the Padang City DPMPTSP, the SINOPEN application is the provision of legality for its intended purpose, not a specific business/activity. This application contains various licensing service features that are not available in OSS services, such as research permits for students or other academics, as well as practice permits for doctors and other health workers throughout the city of Padang.